Matching Learning Styles with Teaching Styles: An Overview (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2013)
Research on learning styles is essential as has been amply demonstrated by modern studies that correct matching of teaching and learning styles often leads to ensuring efficiency and effectiveness and results in positive outcomes for both the students and teachers alike. Catering to the learning preferences of each and every student in a single classroom existing in time and resources constraints is next to the impossible from pragmatic perspectives. Matching learning styles and instructional strategies can improve education and training efficacy. The values based on learners' developing instructional methods that adapt to those patterns expand traction in education, with numerous organizations and businesses offering learning styles as professional development courses for teaching. The study is an overview of the aspects pertaining to and relevant for improving the learners’ accomplishments through the means of matching teaching and learning styles to ensure their compatibility. The theoretical approach consists of examining relevant literature and presenting various views on how to match learning with teaching strategies. It will be determined by a review of the literature and data analysis.